2010
DOI: 10.1093/pcp/pcq115
|View full text |Cite
|
Sign up to set email alerts
|

plenty, a Novel Hypernodulation Mutant in Lotus japonicus

Abstract: Nitrogen fixation in nodules that contain symbiotic rhizobial bacteria enables legumes to thrive in nitrogen-poor soils. However, this symbiosis is energy consuming. Therefore, legumes strictly control nodulation at both local and systemic levels. Mutants deficient in such controls exhibit a range of phenotypes from non-nodulation to hypernodulation. Here, we isolated a novel hypernodulation mutant from the M(2) progeny derived from Lotus japonicus MG-20 seeds mutagenized by irradiation with a carbon ion beam.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…We have identified a putative RDN1 ortholog in the L. japonicus genome database located on chromosome 2 in a region with synteny to the RDN1 region of M. truncatula (Cannon et al, 2006). LjRDN1 lies within the 1.2-cM region of chromosome 2 defined for the L. japonicus PLENTY root-controlled supernodulation locus (Yoshida et al, 2010), suggesting that the plenty mutant phenotype could be caused by a lesion in LjRDN1.…”
Section: Discussion Rdn1 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified a putative RDN1 ortholog in the L. japonicus genome database located on chromosome 2 in a region with synteny to the RDN1 region of M. truncatula (Cannon et al, 2006). LjRDN1 lies within the 1.2-cM region of chromosome 2 defined for the L. japonicus PLENTY root-controlled supernodulation locus (Yoshida et al, 2010), suggesting that the plenty mutant phenotype could be caused by a lesion in LjRDN1.…”
Section: Discussion Rdn1 Mutantsmentioning
confidence: 99%
“…The supernodulation phenotype of sickle mutants, which have disrupted ethylene signaling, demonstrates the role of ethylene in controlling nodulation. The mutants rdh1, tml, and plenty of L. japonicus and nod3 of pea-like har1/sym29/nark/ sunn, form short roots with excessive nodules and nodulate in the presence of nitrate, but the nodulation phenotype of a grafted plant depends on the genotype of the root, not the shoot (Postma et al, 1988;Ishikawa et al, 2008;Magori et al, 2009;Yoshida et al, 2010). None of these mutants appear to have a defect in ethylene signaling.…”
mentioning
confidence: 99%
“…The details of the ion beam irradiation have been reported previously (Oka-Kira et al, 2005;Magori et al, 2009;Yoshida et al, 2010). Seeds were sown in sterilized vermiculite soaked in autoclaved vermiculite supplied with Broughton and Dilworth solution (Broughton and Dilworth, 1971) containing 0.5 mM KNO 3 with or without Mesorhizobium loti MAFF 303099 under a 16-h-light/8-h-dark cycle.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Albeit without ultimate proof, these nodulation-related CLE peptides have been hypothesized to act as the Q signal to activate the CLV-like receptor complex in the shoot for AON. In addition to the CLE peptides, several mutants have been identified that might be affected in genes involved in the control of AON in the root, such as nod3, rdn1, rdh1, tml, and plenty (Postma et al, 1988;Ishikawa et al, 2008;Magori et al, 2009;Novák, 2010;Yoshida et al, 2010;Novák et al, 2011;Schnabel et al, 2011). These mutants might be defective in the genes that control the root-derived signals or the root-to-shoot processing/transducing signals or vice versa (Li et al, 2009;Novák, 2010).…”
mentioning
confidence: 99%